Roles of Copper Transport Systems Members in Breast Cancer - Yichang Chen; Chen Li; Mengxin Li; Bing Han (Cancer Medicine)
ABSTRACT Background The occurrence and progression of breast cancer are closely linked to copper ion homeostasis. Both copper deficiency and excess can inhibit breast cancer growth, while copper transport systems may contribute to its progression by regulating copper ion transport and the activity of associated proteins. However, a comprehensive review of the roles and applications of copper transport systems in breast cancer remains limited. In this study, we summarize the workflow of copper transport systems and the dual role of copper in cancer, highlighting the contributions of specific members of the copper transport system to breast cancer. Methods A comprehensive search of the PubMed database was conducted to identify articles published over the past 30 years that focus on the relationship between copper transport system members and breast cancer. The findings were synthesized to elucidate the roles and mechanisms of these transporters in the onset and progression of breast cancer. Results We identified 13 members of the copper transport system associated with the occurrence, progression, and mortality of breast cancer, including SLC31A1, DMT1, ATP7A, ATP7B, MTs, GSH, ATOX1, CCS, COX17, SCO1, SCO2, and COX11. Our findings revealed that, apart from STEAP, the remaining 12 members were overexpressed in breast cancer. These members influence the onset, progression, and cell death of breast cancer by modulating biological pathways such as intracellular copper ion levels and ROS. Notably, we observed for the first time that depletion of the copper storage protein GSH leads to increased copper ion accumulation, resulting in cuproptosis in breast cancer cells. Conclusion By integrating the members of the copper transport system in breast cancer, we offer novel insights for the treatment of breast cancer and copper‐related therapies.